Can digital finance promote low-carbon transition? Evidence from the People's Republic of China - Xing Ge; Tomoki Fujii (Asian Development Bank Institute (ADBI), 2023)
Using panel data of cities in the People's Republic of China from 2011 to 2019, this paper analyzes the impact of digital finance on low-carbon transition derived from a super-efficiency slacks-based measure data envelopment analysis. We find that digital finance promotes low-carbon transition, and this finding is robust with respect to the choice of sample, potential presence of measurement issue, choice of study period, presence of other policies, and potential endogeneity, among others. This impact, at least in part, is through increased green innovations. We also find evidence for impact heterogeneity across locations and by the level of low-carbon transition. This paper provides policy implications for the low-carbon transition of the region from a digital finance perspective.
Keywords: G20; Q54; Q55; 330; digital finance; low-carbon transition; green innovation; slacks-based measuredata envelopment analysis